Racial Group Affinity and Religious Giving: Evidence from Congregation-Level Panel Data - Valentina Dimitrova-Grajzl; Peter Grajzl; A. Joseph Guse; J. Taylor Smith (Center for Economic Studies and ifo Institute (CESifo), 2014)
Since giving to religious organizations constitutes a substantial portion of total charitable giving, an understanding of the determinants of religious giving is a vital policy concern. Drawing on a novel congregation-level panel dataset, we examine whether religious giving is driven by preferences for racial group affinity, that is, loyalty to one's own racial group. To address endogeneity concerns, we combine a fixed effects estimation framework with an instrumental variable approach. We find robust evidence consistent with the racial group affinity motive: a decrease in the percent of whites in the county is ceteris paribus associated with a decrease in the total giving receipts collected by predominantly white congregations.
Keywords: D64; L31; Z12; J15; 330; religious giving; racial group affinity; diversity; congregations